The evolution of consumer cooperatives in Colombia within a framework of internationalization - Álvarez Rodríguez, Juan Fernando (Universidad Francisco de Paula Santander, 2014)
After thoughtful analysis of two studies on public policy in the field of consumer cooperatives 1980 - 2010 and cooperative internationalization conditions and guidelines for development in Colombia, some elements that contributed the economic outcome of the consumer cooperatives in analyzing the Colombian market. The purpose of this analysis is to identify the factors that most influenced the articulation of consumer cooperatives in the markets, its sectoral presence and the elements to consider in a possible future promotion. This, in the context of a process of rethinking the role of consumer cooperatives as articulators of social welfare, cohesion and generation markets in post- conflict scenarios. As findings to date include: • Internally the bulk of consumer cooperatives were unable to adapt to a dynamic and innovative market entry hypermarkets and compensation funds, encouraged by the State displaced this option organization of consumption. • In the absence of these structures generation via integration scales generated excessive guidance to others who did not provide incentives to